Clinical effect of qingre bawei capsules combined with budesonide in the treatment of acute exacerbation of chronic obstructive pulmonary disease - Sun, Yanli; Ren, Huanxin; Han, Xinrong; Yu, Shuo; An, Hongming; Yang, Xixi (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the clinical effect of Qingre Bawei capsules combined with budesonide in the treatment of acute exacerbation of chronic obstructive pulmonary disease. Method: The retrospective study was conducted at the Baoding No.1 Central Hospital, China, and comprised data of patients with acute exacerbation of COPD admitted between June 1, 2020, and June 30, 2022. The patients were divided into two groups based on treatment methods. The group A had been treated with Qingre Bawei capsules in combination with budesonide, while the group B had been treated with budesonide alone. Both the groups had been treated for 2 consecutive weeks. Compare the changes in blood gas indicators, inflammation indicators, and lung function indicators between two groups of patients before and 24 hours after treatment, and compare the time for clinical symptom disappearance and adverse reactions between the two groups of patients. Results: Of the 120 patients, 60(50%) were in group A; 41(68.3%) males and 19(31.7%) females, with mean age 65.28±4.36 years (range: 47-78 years) and mean course of disease 31.22±4.75 hours (range: 6-65 hours). 60(50%) patients were in group B; 43(71.7%) males and 17(28.3%) females with mean age 65.31±4.31 years (range: 48-78 years) and mean course of disease 31.29±4.71 hours (range: 8-68 hours). The disappearance time of clinical symptoms in group A was better than group B (p<0.05). The levels of blood gas indicators, inflammation indicators, and lung function indicators in both groups significantly improved (p<0.05), but the degree of improvement in group A was better than group B (p<0.05); The total effective rate of group A was better than group B (p<0.05). None of the patients in either group experienced any significant adverse reaction. Conclusion: Qingre Bawei capsules combined with budesonide had a significantly better therapeutic effect on cases of acute exacerbation of chronic obstructive pulmonary disease compared to budesonide alone. Key Words: Qingre Bawei capsules, Budesonide, Acute exacerbation, Chronic obstructive pulmonary disease, Clinical effects.